2014
DOI: 10.1016/j.neurobiolaging.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial permeability transition pore regulates Parkinson's disease development in mutant α-synuclein transgenic mice

Abstract: Parkinson’s disease (PD) is a movement disorder caused by neurodegeneration in neocortex, substantia nigra (SN) and brainstem and synucleinopathy. Some inherited PD is caused by mutations in α-synuclein (αSyn), and inherited and idiopathic PD are associated with mitochondrial perturbations. However, the mechanisms of pathogenesis are unresolved. We characterized a human αSyn transgenic mouse model and tested the hypothesis that the mitochondrial permeability transition pore (mPTP) is involved in the disease me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 130 publications
1
83
0
Order By: Relevance
“…Interestingly, human ␣-synuclein was found to associate with VDAC1 in the brain stem, striatum, and cortex of transgenic mice expressing a pathogenic mutant form (A53T) of human ␣-synuclein (10). The mitochondria associated with human ␣-synuclein A53T appeared to be swollen, an indication of opening of the mitochondrial PTP (10). This finding suggests that increased level of ␣-synuclein in vivo could play a role in opening the mitochondrial PTP.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, human ␣-synuclein was found to associate with VDAC1 in the brain stem, striatum, and cortex of transgenic mice expressing a pathogenic mutant form (A53T) of human ␣-synuclein (10). The mitochondria associated with human ␣-synuclein A53T appeared to be swollen, an indication of opening of the mitochondrial PTP (10). This finding suggests that increased level of ␣-synuclein in vivo could play a role in opening the mitochondrial PTP.…”
Section: Discussionmentioning
confidence: 89%
“…Although the role of mitochondrial permeability transition in PD-related cell death requires further study, two recent reports support the in vivo relevance of our data. Findings from Martin et al (32) indicate that the genetic ablation of cyclophilin D, the mPTP modulator and target of CsA, delayed the onset of mitochondrial abnormalities and neuronal apoptosis in Thy1-␣Syn A53T transgenic mice. Also, Büttner et al (33) showed that overexpression of ␣Syn in yeast led to cell death and a redistribution of the proapoptotic nuclease EndoG from mitochondria to the nucleus, and these effects could both be rescued by genetic modulation of the mPTP components.…”
Section: Discussionmentioning
confidence: 99%
“…␣Syn may associate abnormally with mitochondria in PD patients and animal models (27)(28)(29)(30)(31)(32)(33). An apparent partial subcellular redistribution of ␣Syn from the cytoplasm to the inner and outer mitochondrial membranes (27,34,35) is correlated with mitochondrial dysfunction, including increased oxidative stress, reduced mitochondrial membrane potential (⌬⌿ m ), altered Ca 2ϩ homeostasis, and cytochrome c release (27, 29 -31, 33, 36, 37).…”
Section: ؉mentioning
confidence: 99%
“…Indeed, CypD deletion studies show benefit in mouse models of amyloid lateral sclerosis and Parkinson's diseases as genetic ablation of CypD delayed the onset of disease and extended lifespan (Martin, Semenkow, Hanaford, & Wong, 2014; Martin et al., 2009), strengthening the role of the mPTP in the mechanisms of both diseases. The beneficial effect observed with a novel small mPTP inhibitor in a mouse model of amyloid lateral sclerosis confirmed that the mPTP could represent an interesting target for drug development in amyloid lateral sclerosis (Martin, Fancelli, et al., 2014).…”
Section: Evidence For the Involvement Of Mptp Opening In Age‐associatmentioning
confidence: 99%